1993
DOI: 10.1042/bj2930633
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the CAMPATH-1 antigen, a glycosylphosphatidylinositol-anchored glycoprotein which is an exceptionally good target for complement lysis

Abstract: CAMPATH-1 antibodies recognize a unique molecule on human lymphocytes and are unusually efficient at causing cell lysis with homologous complement. They have been successfully used for lymphocyte depletion in vivo in a variety of diseases. We find that the antigen is a very small glycosylphosphatidylinositol (GPI)-anchored glycoprotein with a mature peptide comprising only 12 amino acids. It can be separated into two distinct antigenic fractions which differ in their susceptibility to phosphatidylinositol-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(114 citation statements)
references
References 44 publications
4
110
0
Order By: Relevance
“…[1][2][3] The C-terminus is anchored on the cell membrane by a glycosylphosphatidylinositol (GPI) lipid. 2,4 CD52 is expressed on the surface of T and B lymphocytes, monocytes/macrophages, eosinophils, and on some early hematopoietic cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The C-terminus is anchored on the cell membrane by a glycosylphosphatidylinositol (GPI) lipid. 2,4 CD52 is expressed on the surface of T and B lymphocytes, monocytes/macrophages, eosinophils, and on some early hematopoietic cells.…”
mentioning
confidence: 99%
“…11 Later studies showed that CAMPATH-1 antibodies recognize CD52. 1,10,12 The immunoglobulin G1 (IgG1) form of CAMPATH-1 was humanized and this agent, alemtuzumab (CAMPATH-1H), was recently approved for the treatment of patients with refractory chronic lymphocytic leukemia (CLL). 13 The CAMPATH-1 family of antibodies is also being used in vitro for lymphocyte depletion in recipients of allogeneic bone marrow grafts, and is being investigated as an immunomodulatory therapy in a variety of diseases.…”
mentioning
confidence: 99%
“…Alemtuzumab binds to CD52, a 12-amino acid cell surface protein of unknown function [10][11][12] that is expressed at high levels on T cells and B cells and at lower levels on monocytes, macrophages, and eosinophils with little found on Natural Killer cells, neutrophils, and hematological stem cells. Cells of the innate immune system are unaffected.…”
Section: Alemtuzumab's Mechanism Of Actionmentioning
confidence: 99%
“…Importantly, however, its expression on CD34 + HSCs is low [27]. Binding of alemtuzumab to CD52 leads to cytotoxicity through different mechanisms, including antibody-mediated cytolysis [28], complement-induced membrane attack complex [29], and apoptosis [30,31]. The cytolytic effects of alemtuzumab lead to prolonged lymphopenia and a complete reconstitution of T-lymphocyte populations may take as long as 5 years [32].…”
Section: Ahsct Mechanism Of Action: the Immunosuppression Hypothesismentioning
confidence: 99%